2022
DOI: 10.1101/2022.05.11.491288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA binding proteins Smaug and Cup induce CCR4-NOT-dependent deadenylation of the nanos mRNA in a reconstituted system

Abstract: Posttranscriptional regulation of the maternal nanos mRNA is essential for the development of the anterior – posterior axis of the Drosophila embryo. The nanos RNA is regulated by the protein Smaug. Binding to Smaug recognition elements (SREs) in the nanos 3’-UTR, Smaug nucleates the assembly of a larger repressor complex including the eIF4E-T paralog Cup and five additional proteins. The Smaug-dependent complex represses translation of nanos and induces its deadenylation by the CCR4-NOT deadenylase. Here we r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 137 publications
(242 reference statements)
2
8
0
Order By: Relevance
“…An intriguing speculation is that the IDRs of Cup may actually facilitate direct binding to osk mRNA, as IDR domains are known to bind mRNAs in other species (Smith et al 2016). This speculation was supported by results of a recent study that suggest that Cup is able to directly bind to mRNAs without any other factors (Pekovic et al 2022). Surprisingly, we also found that Cup-YFP expression was decreased in bru1 RNAi egg chambers and the YFP signal was no longer concentrated in the oocyte (Fig.…”
Section: Bru1 and Cup Maintain A Stable Association With Osk Mrna In ...supporting
confidence: 75%
“…An intriguing speculation is that the IDRs of Cup may actually facilitate direct binding to osk mRNA, as IDR domains are known to bind mRNAs in other species (Smith et al 2016). This speculation was supported by results of a recent study that suggest that Cup is able to directly bind to mRNAs without any other factors (Pekovic et al 2022). Surprisingly, we also found that Cup-YFP expression was decreased in bru1 RNAi egg chambers and the YFP signal was no longer concentrated in the oocyte (Fig.…”
Section: Bru1 and Cup Maintain A Stable Association With Osk Mrna In ...supporting
confidence: 75%
“…To assess protein interactions with Smaug we used an EGFP-Smaug construct that carried an N-terminal fusion to a PH domain (Salgania et al , 2022), which directed the localization of Smaug to the plasma membrane. With the ReLo assay, we have previously evaluated the interaction between Smaug and the six core subunits of the CCR4-NOT deadenylase complex, which is responsible for the deadenylation of nanos mRNA, and have identified the NOT3 subunit as Smaug-binding protein (Pekovic et al , 2022). Here, we tested interactions between Smaug and additional proteins involved in nanos mRNA repression, including Ago1 and Ago2 (Pinder and Smibert, 2013), Aubergine and Ago3 (Barckmann et al , 2015; Rouget et al , 2010), Cup (Nelson et al , 2004) as well as Me31B, Tral, and Belle (Götze et al , 2017; Jeske et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…All other ReLo cloning vectors were described previously (Salgania et al , 2022; Jeske et al , 2017; Behm-Ansmant et al , 2006). The Y2H cloning vectors were described previously (Pekovic et al , 2022; Jeske et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations